Eine Abschätzung des Restgliedes im Primzahlsatz des Gaussschen Zahlenkörpers - Vaitkevičius, J. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Вайткявичюс. Одна оценка остаточного члена асимптотического закона распределения простых чисел Гауссова поляJ. Vaitkevičius. Gauso kūno pirminių skaičių asimptotinio pasiskirstymo dėsnio liekamojo nario įvertinimas